2017
DOI: 10.17221/124/2016-swr
|View full text |Cite
|
Sign up to set email alerts
|

Comparing measurements, <sup>7</sup>Be radiotracer technique and process-based erosion model for estimating short-term soil loss from cultivated land in Northern Germany

Abstract: Deumlich D., Jha A., Kirchner G. (2017): Comparing measurements,7 Be radiotracer technique and process-based erosion model for estimating short-term soil loss from cultivated land in Northern Germany. Soil & Water Res., 12: 177−186.Due to changing climate and irregular weather patterns, event-based soil loss and sediment yield have become important issues in the agricultural areas. Several mathematical models and prediction methodologies have been used to estimate event-based soil loss and soil redistribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…These authors found the IC increased for a given pixel when the pixel size decreased. After value normalisation, our results agreed with those of Cantreul et al for DEM resolutions from 1 to 0.2 m, and disagreed over a range of 0.2 to 0.05 m. However, the IC values at the outlet concurred with other hydrological connectivity and soil erosion modelling studies: (i) Habtezion et al (2016) examined the effects of nine DEM resolutions on watershed hydrologic modelling, from 0.02 to 0.8 m, in a small experimental field plot and observed that lower DEM resolutions tended to eliminate topographic features and thus surface depression storage was less represented; this leads to an overestimation of hydrological connectivity; and (ii) Deumlich et al (2017), using the EROSION-3D model in two cultivated plots, predicted decreasing median values of soil erosion with increasing resolution (25, 10, 5, 2 and 1 m). The actual width of some microtopographic connections (rills and ephemeral gullies), which is similar to cell size (from rills a few centimetres wide to ephemeral gullies with a width of 20 to 30 cm), may explain our results and how they compare to other studies.…”
Section: Structural and Functional Connectivity And Optimum Dem Resolsupporting
confidence: 79%
“…These authors found the IC increased for a given pixel when the pixel size decreased. After value normalisation, our results agreed with those of Cantreul et al for DEM resolutions from 1 to 0.2 m, and disagreed over a range of 0.2 to 0.05 m. However, the IC values at the outlet concurred with other hydrological connectivity and soil erosion modelling studies: (i) Habtezion et al (2016) examined the effects of nine DEM resolutions on watershed hydrologic modelling, from 0.02 to 0.8 m, in a small experimental field plot and observed that lower DEM resolutions tended to eliminate topographic features and thus surface depression storage was less represented; this leads to an overestimation of hydrological connectivity; and (ii) Deumlich et al (2017), using the EROSION-3D model in two cultivated plots, predicted decreasing median values of soil erosion with increasing resolution (25, 10, 5, 2 and 1 m). The actual width of some microtopographic connections (rills and ephemeral gullies), which is similar to cell size (from rills a few centimetres wide to ephemeral gullies with a width of 20 to 30 cm), may explain our results and how they compare to other studies.…”
Section: Structural and Functional Connectivity And Optimum Dem Resolsupporting
confidence: 79%
“…In the Parisian Basin of France, Chartin et al (2013) demonstrated the dominating role of tillage erosion. Particularly areas of a hummocky topography with short summit-footslope distances, such as young morainic areas, can be subject to pronounced in-field soil degradation patterns caused by tillage erosion (Winnige, 2004;Deumlich et al, 2017). Young morainic areas that are under intense arable cultivation and associated tillage erosion are widespread in northern Europe, Canada, the northern USA, Russia and eastern Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…Especially anthropogenic radionuclides (e.g. 137 Cs, 239+240 Pu, 210 Pb, 7 Be) have demonstrated their ability to determine changes in topography (Mabit et al, 2014;Alewell et al, 2017;Deumlich et al, 2017). The force of atmospheric nuclear weapon tests transported radioisotopes outside the troposphere, where circulation led to a (regionally) homogeneous spatial distribution and subsequent fallout on soils via precipitation (Meusburger et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Van pointed out that tillage erosion rates are globally at least in the same order of magnitude as water erosion rates. Particularly areas of a hilly topography with short summit-footslope distances, such as young morainic areas, can be subject to pronounced in-field soil degradation patterns caused by tillage erosion (Winnige, 2004;Deumlich et al, 2017). Young morainic areas that are under intense arable cultivation and corresponding tillage erosion are widespread in northern Europe, Canada, northern USA, Russia and eastern Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…Especially anthropogenic radionuclides (e.g. 137 Cs, 239+240 Pu, 210 Pb, 7 Be) have demonstrated their ability to determine changes in topography (Parsons and Foster, 2011;Alewell et al, 2017;Deumlich et al, 2017). Nuclear weapon tests lifted radioisotopes up to the stratosphere, where mixture led to an almost homogeneous distribution and corresponding fallout by rain (Alewell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%